Polymers derived from leguminous plants: Moringa (Moringa oleifera), Algarrobo (Prosopis spp), Orejero (Enterolobium cyclocarpum) and acacia forrajera (Leucaena leucocephala) and its application in the food industry - Verhelst Salazar, Adriana Lucia
In recent years, the importance of preserving the environment has been emphasized, therefore it is crucial to maintain biodiversity and reevaluate native species, especially trees from which food can beobtained or used at an industrial level, (Ramachandran, 2007) . Therefore, underutilized species have been considered, among them, moringa, carob, acacia and earmuff, because they have an important potential, since the seeds of legumes develop an endosperm composed of polysaccharides that serve as a reserve for energy and water The endosperm of these seeds is composed of galactomannans that are neutral polysaccharides formed by a linear chain of mannose with lateral substitutions of galactose in different proportions, their properties serve to thicken and stabilize emulsions. (Wielinga, 2000; Azero and Andrade, 2002). Plant-derived polymers have recently generated interest due to their various pharmaceutical applications as diluents, binders, disintegrants in tablets, thickeners in oral liquids, protective colloids in suspensions, gelling agents in gels and suppository bases (Zatz and Kushla, 1989); They are also used in cosmetics, textiles, paints and papermaking (Jani, Shah, Prajapati, and Jain, 2009). These materials include: guar gum, isapghula peel, Mimosa scabrella galactomannan, Gleditsia triacanthos Linn (locust bean gum), Sesbania gum, Hibiscus esculenta pod mucilage, copal gum and dammar gum, konjac agar, chitosan, etc. (Efentakis & Kouttis, 2001).